Mismatch Repair of DNA Replication Errors Contributes to Microevolution in the Pathogenic Fungus Cryptococcus neoformans - Boyce, Kylie J. (mBio, 2017)
The ability to adapt to a changing environment provides a selective advantage to microorganisms. In the case of many pathogens, a large change in their environment occurs when they move from a natural setting to a setting within a human host and then during the course of disease development to various locations within that host. Two clinical isolates of the human fungal pathogen Cryptococcus neoformans were identified from a collection of environmental and clinical strains that exhibited a mutator phenotype, which is a phenotype which provides the ability to change rapidly due to the accumulation of DNA mutations at high frequency. Whole-genome analysis of these strains revealed mutations in MSH2 of the mismatch repair pathway, and complementation confirmed that these mutations are responsible for the mutator phenotype. Comparison of mutation frequencies in deletion strains of eight mismatch repair pathway genes in C. neoformans showed that the loss of three of them, MSH2, MLH1, and PMS1, results in an increase in mutation rates. Increased mutation rates enable rapid microevolution to occur in these strains, generating phenotypic variations in traits associated with the ability to grow in vivo, in addition to allowing rapid generation of resistance to antifungal agents. Mutation of PMS1 reduced virulence, whereas mutation of MSH2 or MLH1 had no effect on the level of virulence. These findings thus support the hypothesis that this pathogenic fungus can take advantage of a mutator phenotype in order to cause disease but that it can do so only in specific pathways that lead to a mutator trait without a significant tradeoff in fitness.